INDIKATOR DAN METODE PENGUKURAN KINERJA SMART CITY : TINJAUAN LITERATUR - Ghefira Nur Fatima; Muhayat; Siti Alayda Azzahro (AI Society & STMIK Indonesia, 2026)
This study examines the evolution of smart city performance measurement, focusing on the development of concepts, the types of indicators applied, the measurement methods used, and the challenges found in this field through a comprehensive review of previous studies. The research analyzes 25 journal articles indexed in Scopus and SINTA that discuss topics such as smart city indicators, composite indices, Internet of Things (IoT), network Quality of Service (QoS), resilience, cybersecurity, and governance. The data were analyzed using thematic-comparative analysis and configurational analysis to identify conceptual patterns and methodological differences across the studies. The findings indicate a shift from technology-centered measurement models toward more comprehensive frameworks that incorporate multiple dimensions, including environmental, economic, mobility, governance, social, and digital infrastructure aspects. Differences in data normalization, weighting, index aggregation, and IoT-based data collection influence the accuracy and interpretability of performance assessments. The study also highlights the need to integrate cybersecurity, system reliability, and stakeholder collaboration to develop more robust and context-appropriate smart city evaluation frameworks.